2009
DOI: 10.1073/pnas.0812697106
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ε4 is associated with disease-specific effects on brain atrophy in Alzheimer's disease and frontotemporal dementia

Abstract: Apolipoprotein 4 (apoE4) has been strongly linked with Alzheimer's disease (AD) and contributes to several other neurological disorders. We investigated the influence of 4 allele carrier status on the pattern of gray matter atrophy and disease severity in 51 patients with probable AD and 31 patients with behavioral variant frontotemporal dementia (bvFTD), compared with 56 healthy controls. Voxel-based morphometry was performed by using statistical parametric mapping. The 4 allele frequency was higher in the AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
154
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 160 publications
(169 citation statements)
references
References 42 publications
(42 reference statements)
12
154
2
Order By: Relevance
“…Although several studies have not found psychometric measures favoring carriers (18,20,27), a few reports accord well with the present data. For example, van der Vlies et al (25) reported remarkably similar findings in which noncarriers performed more poorly than carriers on an object naming task and parts A and B of the Trail Making Test.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Although several studies have not found psychometric measures favoring carriers (18,20,27), a few reports accord well with the present data. For example, van der Vlies et al (25) reported remarkably similar findings in which noncarriers performed more poorly than carriers on an object naming task and parts A and B of the Trail Making Test.…”
Section: Resultssupporting
confidence: 81%
“…Conflicting results have also been reported from the limited investigations of cortical anatomy, with some studies reporting no difference and others reporting more robust regional atrophy in ε4 carriers (20,23). Finally, there are a few reports of greater atrophy in noncarriers either in select regions, such as the frontal lobe, or in global measures of brain volume (17,(19)(20)(21).…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…In the authors' view, the changes support the idea that default networks are compromised in AD, and they could also serve as a marker to monitor disease progression or treatment. For another, Maria Gorno-Tempini and colleagues in the U.S. and Italy used MRI scans to examine the relationship between ApoE status and brain atrophy in AD and behavioral variant FTD (bvFTD) [9]. While there is an established link between the ε4 variant of ApoE and brain atrophy in AD, the researchers now extend this link to bvFTD as well, supporting the idea that ApoE4 may be a risk factor for multiple neurodegenerative diseases.…”
Section: Measuring Gross Brain Changes In Ad Ftdmentioning
confidence: 95%